GAMBARAN PENGETAHUAN IBU HAMIL TENTANG TEKNIK MENYUSUI YANG BENAR DI DUSUN ABDI GUNA LANGKAT TAHUN 2021 - Rahmawani Fauza (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2021)
Breastfeeding is an art that must be relearned. All it takes is patience, time, a little knowledge about breastfeeding, and support from the environment, especially the husband. A study in Ghana published in the journal Pediatrics showed 16% of infant deaths could be prevented through breastfeeding the baby from the first day of birth. This figure increases to 22% if breastfeeding begins within the first hour after the birth of the baby. This research is descriptive using primary data, and the sample used is random sampling with a population of 34 respondents and a sample of 30 respondents. From the results of the study, it is known that based on knowledge the majority of respondents have less knowledge as many as 16 respondents (53.33%), while the minority with good knowledge are 5 respondents (16.67%). Based on the age of pregnant women with less knowledge, the majority at the age of 21-30 years as many as 9 respondents (30%) and the minority of pregnant women with sufficient knowledge at the age of <20 years as many as 1 respondent (3.33%). 9 respondents (30%) in high school and a minority of pregnant women with good knowledge in elementary school as many as 1 respondent (3.33%). Based on information sources, the majority of pregnant women have less knowledge of the mass media as many as 13 respondents (43.33%) and the minority with good knowledge of health workers as many as 1 respondent (3.33%) and sufficient knowledge of the mass media as many as 1 respondent (3.33% ). It is hoped that health workers will provide more information about health education or counseling for pregnant women to understand the correct breastfeeding technique and how to breastfeed properly.